Book Review: Telepractice in Audiology - VENTO, BARBARA A. (Int J Telerehabil, 2016)
This article presents a review of the book Telepractice in Audiology, authored by Emma Rushbrooke MPhil(AUD), BA, DipAud., MAudSA., LSLS. Cert. AVT, RNC, and K. Todd Houston, PhD, CCC-SLP, LSLS Cert. AVT, and 13 contributing authors. This is the first book entirely devoted to tele-audiology. It provides practical information for working with clients across the lifespan and for multiple practice settings. Reviewer Dr. Barbara Vento endorses this work as a comprehensive resource on the topic of teleaudiology for both students and aspiring teleaudiologists.